Clinical and radiological postoperative evaluation of posterior sagittal anorectoplasty in patients with upper and intermediate anorectal malformations - Martins, José Luiz; Lederman, Henrique Manoel; Pinus, José (São Paulo Medical Journal, 1997)
The PSARP is today the most-used surgical technique for correction of high and intermediary anorectal malformations.There is much controversy in the literature about the post-operative evaluation of these cases. We studied 27 cases of anorectal malformations from clinical and radiological aspects, in order to analyse: 1. Fecal continence 2.Relationship between post-operative fecal continence and the associated sacral anomalies 3.Relationship between the radiological evaluation by defecogram and fecal continence From the analysis of the cases, we concluded: 1. Fecal continence was achieved in 48.14% of the cases; partial continence in 25.92%; and fecal incontinence in 25.92% of the cases. 2.The presence of fecal incontinence was directly related to the associated sacral anomalies.